2021
DOI: 10.3390/scipharm89030031
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial, Antibiofilm, and Antischistosomal Activity of Montrichardia linifera (Arruda) Schott (Araceae) Leaf Extracts

Abstract: With a broad ethnopharmacological tradition in Brazil, Montrichardia linifera has been reported as a potent antirheumatic, antimicrobial, and antiprotozoan agent. However, there is a lack of studies on its effect on bacterial biofilm formation and Schistosoma mansoni worms. This study reports the effects of antibacterial, antibiofilm, and antischistosomal properties of leaf extracts of M. linifera. Phytochemical screening and identification of the main compounds of the extracts were performed. All the extracts… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
1
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 51 publications
0
1
0
4
Order By: Relevance
“…This was in accordance with previous data, mentioning the presence of flavonoids, tannins, alkaloids, and saponins in M. arborescens leaf 16 and of alkaloids, flavonoids, coumarins, tannins, triterpenes, p-hydroxybenzaldehyde, and steroids in stem and leaf of M. linifera. 32,[39][40][41][42][43][44] Several studies have reported that these compounds -either from various plant parts or as ingredients of plant extracts or enriched herbal preparations -exerted both anti-inflammatory and antioxidant activities in various in vitro, cell culture, and animal models (see, for instance, references). [45][46][47][48][49][50] Summarizing, the results from the current study provide evidence that the fresh M. arborescens stem juice possesses considerable membranestabilizing and antioxidant activities, and contains phytochemicals that may be associated with these activities.…”
Section: Discussionmentioning
confidence: 99%
“…This was in accordance with previous data, mentioning the presence of flavonoids, tannins, alkaloids, and saponins in M. arborescens leaf 16 and of alkaloids, flavonoids, coumarins, tannins, triterpenes, p-hydroxybenzaldehyde, and steroids in stem and leaf of M. linifera. 32,[39][40][41][42][43][44] Several studies have reported that these compounds -either from various plant parts or as ingredients of plant extracts or enriched herbal preparations -exerted both anti-inflammatory and antioxidant activities in various in vitro, cell culture, and animal models (see, for instance, references). [45][46][47][48][49][50] Summarizing, the results from the current study provide evidence that the fresh M. arborescens stem juice possesses considerable membranestabilizing and antioxidant activities, and contains phytochemicals that may be associated with these activities.…”
Section: Discussionmentioning
confidence: 99%
“…Dentre as atividades biológicas mencionadas para Araceae estão: antibacteriana (Miranda et al, 2015), antiesquistossomótica, antibiofilme (Lima et al, 2021), antirreumática (Plowman, 1969), antioxidantes (Aliyu et al, 2013), ação anti-inflamatória (Bacchus, 2016), antinociceptiva (Batista et al, 2019), dentre outras. Na medicina popular, são citadas algumas atividades e que são corroboradas com estudos, como o de Batista et al (2019), que foi realizado na raiz e no rizoma de Montrichardia linifera Arruda (Schott) (uma macrófita aquática), onde foram encontrados substâncias nos concentrados voláteis da planta, como ácidos graxos, alcaloides, alcanos, álcoois, aldeídos, cetonas, diterpenos, ésteres, fenilpropanoides, hidrocarbonetos, lactonas, norisoprenoides, piranos, sesquiterpenos e terpenos, o que sustenta o uso da planta em tratamentos antifúngico de impingem e de frieira, por indígenas e ribeirinhos.…”
Section: Introductionunclassified
“…Montrichardia linifera está entre as espécies que possuem atividade bacteriana comprovada contra bactérias Grampostivas e Gram-negativas (MIRANDA et al, 2015) e ação anti-helmíntica, contra esquistossomose (Lima et al, 2021).…”
Section: Introductionunclassified
“…Esta ampla utilização popular da aninga resultou em pesquisas para investigações de suas bioatividades através de ensaios padronizados e validados cientificamente, tais como atividade antiplasmódica e antibacteriana, e baixa toxicidade contra Artemia salina (Costa et al, 2009;Amarante et al, 2011ac;Miranda et al, 2015;Lima et al, 2021) e, atividade antipromastigota (Silva-Silva, et al, 2017), propriedades antioxidantes, citotóxicas e cicatrizantes (Santos, et al, 2014).…”
unclassified